PENINGKATAN KARAKTER GOTONG ROYONG SISWA MELALUI MODEL PEMBELAJARAN KOOPERATIF PADA MATA PELAJARAN PENDIDIKAN PANCASILA DI KELAS VI SDN 1 CIEURIH - Ujang Endang; Daryaman; Bella Oktavia; Nurul Aisyah; Rio Ramdani; Tsuraya Balqis (CV. Kalimasada Group, 2026)
The gotong royong (mutual cooperation) character of students remains a critical concern in Pancasila Education at the elementary school level, particularly in the context of the Merdeka Curriculum and the Profil Pelajar Pancasila framework. This Classroom Action Research (CAR) aimed to improve the gotong royong character of Grade VI students at SDN 1 Cieurih through the implementation of a cooperative learning model. The research was conducted over two cycles, each comprising planning, action, observation, and reflection stages following the Kemmis and McTaggart model. Participants were 19 students (10 male, 9 female). Data were collected through observation, interviews, and documentation, and analyzed using descriptive quantitative percentage techniques. The findings showed a progressive increase in the gotong royong character from a mean score of 61% in the pre-cycle to 66% in Cycle I and 73% in Cycle II. The proportion of students achieving the Good or Very Good category increased from 11% (pre-cycle) to 32% (Cycle I) and 53% (Cycle II), indicating significant improvement across all three indicators: mutual assistance (tolong-menolong), solidarity (solidaritas), and mutual respect (saling menghargai). These results demonstrate that cooperative learning effectively stimulates collaborative values and supports the implementation of the Profil Pelajar Pancasila, though further cycles are recommended to fully achieve the 75% categorical success criterion.